2021
DOI: 10.3389/fgene.2021.769888
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Major Facilitator Superfamily and Its Expression in Response of Poplar to Fusarium oxysporum

Abstract: The major facilitator superfamily (MFS) is one of the largest known membrane transporter families. MFSs are involved in many essential functions, but studies on the MFS family in poplar have not yet been reported. Here, we identified 41 MFS genes from Populus trichocarpa (PtrMFSs). We built a phylogenetic tree, which clearly divided members of PtrMFS into six groups with specific gene structures and protein motifs/domains. The promoter regions contain various cis-acting elements involved in stress and hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…This role has been proven in several studies through the artemisinin yield in Artemisia annua [ 80 ], the expression of PDR-type ABC transporter gene PgPDR3 in Panax ginseng [ 81 ], and the expression of a large proportion of ABC transporters in Lycoris aurea [ 77 ], under MeJA treatment. As well, it has demonstrated that the major facilitator superfamily (MFS) is necessary for plant tolerance against Fusarium oxysporum in Populus trichocarpa [ 82 ] and strong light in Arabidopsis [ 83 ], while their role has not assessed against MeJA treatment yet. In addition to these results, a large proportion of ABC transporters, which are subfamily of primary active transporters system based on the TCDB, were identified in MeJA-treated R .…”
Section: Discussionmentioning
confidence: 99%
“…This role has been proven in several studies through the artemisinin yield in Artemisia annua [ 80 ], the expression of PDR-type ABC transporter gene PgPDR3 in Panax ginseng [ 81 ], and the expression of a large proportion of ABC transporters in Lycoris aurea [ 77 ], under MeJA treatment. As well, it has demonstrated that the major facilitator superfamily (MFS) is necessary for plant tolerance against Fusarium oxysporum in Populus trichocarpa [ 82 ] and strong light in Arabidopsis [ 83 ], while their role has not assessed against MeJA treatment yet. In addition to these results, a large proportion of ABC transporters, which are subfamily of primary active transporters system based on the TCDB, were identified in MeJA-treated R .…”
Section: Discussionmentioning
confidence: 99%
“…MFS transporters, in addition to sugar influx (Pereira et al 2013 ; Ramón-Carbonell and Sánchez-Torres 2017 ; Vela-Corcía et al 2019 ), may also efflux toxic compounds and thus promote fungicide resistance (Costa et al 2014 ; Popiel et al 2017 ) and interspecific competition (Malmierca et al 2013 ). These transporters have also been shown to be responsible for the efflux of plant antimicrobial compounds (isothiocyanates) from Botrytis cinerea (Vela-Corcía et al 2019 ) and for promoting the virulence of many phytopathogenic fungi (Hayashi et al 2002 ; Choquer et al 2007 ; Roohparvar et al 2007 ; Omrane et al 2017 ; Popiel et al 2017 ; Vela-Corcía et al 2019 ; Diao et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%